Firm characteristics, capabilities and productivities: A study of Malaysian food manufacturing sector / Lim Tien Hong - Lim , Tien Hong (2020)
This research establishes and examines a set of firm productivity measures for the Malaysian food manufacturing industry. The research further examines the differences in productivity based on the firm’s characteristics and consequently examines the empirical relationship between firm capabilities namely marketing, ICT, R&D and human capital on labour productivity. The research uses cross sectional data comprising 1020 firms. Various methods were used in the research. Non-parametric analysis was undertaken to compare the productivity levels across firm characteristics while in examining the impact of capabilities on labour productivity the research uses quantile regression analysis. The finding shows that productivity differs based on firm legal status and size of enterprises only influence capital and labour productivities. Meanwhile, energy and material productivities differ mostly across industry types. Firm’s ownership only influences labour productivity of food manufacturing. The results of the quantile regressions are as follows. The findings showed that size becomes less relevant at the higher tail of the quantile and as capabilities and human capital grows, productivity gains are much higher. The findings are robust to different measures of human capital and capabilities. Interestingly, among the capabilities, innovation matters the most in driving labour productivity. ICT capability, on the other hand, matters for firm in the lower quantile suggesting that investment in only several common technologies such as computers and information technology platforms will not be adequate once firms are in the higher quantile of the productivity. As for marketing capability, it shows that market creating capability of the firms enhances productivity. Nevertheless, the coefficient does not vary across the lower and upper productivity quantile. The study concludes with implications for driving labour productivity across capabilities through policy recommendations to raise human capital and improve ICT infrastructure and working conditions.